The Impact of Collaborators on the Quality of Translation: A Study on Translating Chinese Texts into Indonesian - Jessica Irawan; Daniel Ginting (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
The study aimed to investigate the role of translation collaborators in translating Chinese texts into Indonesian and to evaluate the quality of translations from Mandarin into Indonesian. An analytic scoring rubric was utilized to assess the quality of the translations in terms of grammar, vocabulary, readability, and tone. The study found that there is no significant difference between the mean scores of texts translated by an individual translator and those translated collaboratively. The authors identified that the number of source texts, content of the translation, structure of the text, and readability of the output contribute to the similarity in quality between the two methods. However, factors such as editing and correction, time frame, and supporting tools (sources) make the translation process different between the two methods. The study also found that the duration needed for collaborative translation is relatively shorter compared to translating individually, and collaborative translation can result in faster completion times and improved accuracy and readability of translated texts